"Olfactory Three-Needle" Enhances Spatial Learning and Memory Ability in SAMP8 Mice. (2nd January 2020) - Wang, Yuan; Wang, Qiang; Ren, Bo; Guo, Ting; Qiang, Jing; Cao, Hui; Gao, Yujie; Liu, Zhibin; Gao, Xinyan; Zhu, Bing
Abstract : As one of the most important therapies in complementary and alternative medicine, acupuncture has been used in the treatment of Alzheimer's disease (AD). Acupuncture of "olfactory three-needle" manipulation can improve the cognitive ability of AD patients. However, the mechanism of "olfactory three-needle" in AD remains largely unknown. Here, we identified that the "olfactory three-needle" therapy and eugenol olfactory stimulation both reduced the deposition of β -amyloid (A β ) protein and increased the expression of synaptophysin (SYP), but only the "olfactory three-needle" enhanced the spatial learning and memory ability of SAMP8. Remarkably, the "olfactory three-needle" inhibited the phosphorylation of p38MAPK and the excessive activation of microglia (MG) in the hippocampus. Our study demonstrates that the "olfactory three-needle" enhances spatial learning and memory ability by inhibiting the phosphorylation of p38MAPK and the excessive activation of MG to reduce the neuroinflammatory response and neurotoxicity of A β and promote synaptic regeneration, but it was not completely consistent with the stimulation of the olfactory system.